2014
DOI: 10.1007/s00253-014-5987-x
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme A-transferase-independent butyrate re-assimilation in Clostridium acetobutylicum—evidence from a mathematical model

Abstract: (2014) Coenzyme A-transferaseindependent butyrate re-assimilation in Clostridium acetobutylicum -evidence from a mathematical model. Applied Microbiology and Biotechnology, 98 (21 A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
3
12
0
Order By: Relevance
“…However, in the rex deletion mutant butyrate is visibly reassimilated which in the pathway proposed by Malaviya et al (2012) is coupled to acetone formation via the acetoacetyl- CoA: butyrate:CoA transferase in a similar fashion to C. acetobutylicum (Jones and Woods, 1986). These findings suggest that C. pasteurianum may be able to reassimilate butyrate without the need of acetone production either through the reverse reaction of the butyrate kinase ( buk ) and the phosphotransbutyrylase ( ptb ), as previously suggested (Hüsemann and Papoutsakis, 1989, Millat et al, 2014), or via a third, as yet undescribed, mechanism proposed by Millat et al (2014). Reassimilation of butyrate without acetone production has been described in several C. acetobutylicum inactivational mutants, most notably mutants of ctfA (Millat et al, 2014), ptb (phosphotransbutrylase) and adc (acetoacetate decarboxylase) (Lehmann et al, 2012) and butyrate kinase ( buk ) gene (Desai et al, 1999).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, in the rex deletion mutant butyrate is visibly reassimilated which in the pathway proposed by Malaviya et al (2012) is coupled to acetone formation via the acetoacetyl- CoA: butyrate:CoA transferase in a similar fashion to C. acetobutylicum (Jones and Woods, 1986). These findings suggest that C. pasteurianum may be able to reassimilate butyrate without the need of acetone production either through the reverse reaction of the butyrate kinase ( buk ) and the phosphotransbutyrylase ( ptb ), as previously suggested (Hüsemann and Papoutsakis, 1989, Millat et al, 2014), or via a third, as yet undescribed, mechanism proposed by Millat et al (2014). Reassimilation of butyrate without acetone production has been described in several C. acetobutylicum inactivational mutants, most notably mutants of ctfA (Millat et al, 2014), ptb (phosphotransbutrylase) and adc (acetoacetate decarboxylase) (Lehmann et al, 2012) and butyrate kinase ( buk ) gene (Desai et al, 1999).…”
Section: Discussionsupporting
confidence: 70%
“…These findings suggest that C. pasteurianum may be able to reassimilate butyrate without the need of acetone production either through the reverse reaction of the butyrate kinase ( buk ) and the phosphotransbutyrylase ( ptb ), as previously suggested (Hüsemann and Papoutsakis, 1989, Millat et al, 2014), or via a third, as yet undescribed, mechanism proposed by Millat et al (2014). Reassimilation of butyrate without acetone production has been described in several C. acetobutylicum inactivational mutants, most notably mutants of ctfA (Millat et al, 2014), ptb (phosphotransbutrylase) and adc (acetoacetate decarboxylase) (Lehmann et al, 2012) and butyrate kinase ( buk ) gene (Desai et al, 1999). The fact that C. pasteurianum does not produce acetone under any condition tested here, or elsewhere (Biebl, 2001, Pyne et al, 2016, Sandoval et al, 2015), makes this organism an ideal target for investigations of the butyrate and acetate uptake mechanisms not reliant on CtfAB.…”
Section: Discussionsupporting
confidence: 70%
“…A strain with clostron inactivated ctfAB genes was previously constructed [ 21 ]. From the physiological analysis of this mutant and with the help of a mathematical model [ 22 ], it was demonstrated that butyrate was mainly reconsumed by the phosphotransbutyrylase-buyrate-kinase pathway and not by the acetoacetyl-CoA:acetate CoA-transferase in agreement with the data presented in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Haus et al [ 40 ] presented a kinetic model that considered some of the important enzymes in continuous culture and their pH dependence. The latter kinetic model was extended in [ 41 43 ] to include the role of cell population dynamics as well as other enzymes involved in the metabolic shift from acidogenesis to solventogenesis. These kinetic models, however, provide limited investigation into the effects of process and kinetic parameters on the systems-level fermentation.…”
Section: Introductionmentioning
confidence: 99%